Core stability training and young para-swimmers' results on 50 meters and 100 meters freestyle - Jakubczyk, N.; Zwierzchowska, A.; Maszczyk, A. (Baltic Journal of Health and Physical Activity, 2019)
Central stabilization training aims to improve neuromuscular coordination. It is used to prevent injuries and complement swimmers` training process. The aim of the study was to access the impact of this training on the results by disabled swimmers at 50 and 100 meters` freestyle. Material/Method: 20 competitors with similar dysfunctions of the musculoskeletal system, randomly assigned to an experimental and a control group, participated in the study. Each group consisted of 7 swimmers starting in competitions from the standing starting position and 3 starting from water. The study included a 4-week set of stabilization exercises, 4 times a week instead of pulling by legs. Exercises were performed under specialist swimming conditions and involved controlled circuit muscles movements, while maintaining a floating stable position in the water. Results: All groups improved their "best times", besides swimmers starting from the standing position in the control group. There were no significance differences between intergroup and intra-group results, both at distance 50 and 100 meters` freestyle. Conclusions. Better improvements in the experimental group were noted, but this effect cannot be attributed to 4-week stabilization training. However, this investigation might suggest that this type of training could be beneficial for junior disabled swimmers.